Enterprise-industry coevolution : a value-based perspective - Massey, Brian P. (Trinity College (Dublin, Ireland). Trinity Business School, 2014)
The motivation driving this research project was the desire to better understand the interaction of strategy, entrepreneurship and industry evolution. At the outset of this research, there was no integrated conceptual framework connecting these domains of knowledge. However, there has long been acknowledgement that these domains are closely related. In order to advance theory and better inform practice, this project was launched to study the interrelated nature of change between the processes of strategy, entrepreneurship and industry evolution.
Embargo End Date: 2020-02-01
Keywords: Business, Ph.D.; Ph.D. Trinity College Dublin, 2014